Kuwait : 2019 Article IV Consultation; Press Release; Staff Report; and Statement by the Executive Director for Kuwait. (IMF Staff Country Reports; Country Report ;, 2019)
This Article IV Consultation highlights that growth has strengthened, and fiscal and external positions improved due to higher oil prices. The increased uncertainty about oil price prospects though underscores the need to reduce dependence on oil and increase savings for the future. The key priority is to build national consensus around equitable and well-sequenced reforms to underpin fiscal consolidation and promote the private sector. While authorities' efforts to strengthen the fiscal accounts are welcomed, more ambitious reforms will be needed to secure adequate savings for future generations and reduce financing needs. Reforming the public wage bill, subsidies, and transfers, raising non-oil revenue, and enhancing the fiscal policy framework and governance are expected to support fiscal consolidation and increase the efficiency of spending on human and physical capital. Creating jobs for the large number of nationals joining the labor force over the next decade hinges on the emergence of a vibrant private sector.